Who Fears Competition from Informal Firms? Evidence from Latin America - González, Alvaro S.; Lamanna, Francesca (World Bank, Washington, DC, 2012)
This paper investigates who is most affected by informal competition and how regulation and enforcement affect the extent and nature of this competition. Using newly-collected enterprise data for 6,466 manufacturing formal firms across 14 countries in Latin America, the authors show that formal firms affected by head-to-head competition with informal firms largely resemble them. They are small credit constrained, underutilize their productive capacity, serve smaller customers, and are in markets with low entry costs. In countries where the government is effective and business regulations onerous, formal firms in industries characterized by low costs to entry feel the sting of informal competition more than in other business environments. Finally, the analysis finds that in an economy with relatively onerous tax regulations and a government that poorly enforces its tax code, the percentage of firms adversely affected by informal competition will be reduced from 38.8 to 37.7 percent when the government increases enforcement to cover all firms.